Paradoks Kembar (Twin Paradox): Analisis dan Resolusi dalam Kerangka Teori Relativitas Khusus - M. Fadly; Hizkia Natanael Simatupang; Yanti Seniawati Aritonang; Amisha Sihite; Elisa Siregar; Jujur Marholong Purba; Deo Demonta Panggabean; Ladestam Sitinjak (Universitas Hamzanwadi, 2026)
The Twin Paradox stands as one of the most challenging thought experiments in Einstein's special theory of relativity, seemingly revealing an internal contradiction within the theory itself. This paradox illustrates the scenario of twin siblings where one travels through space at relativistic speeds while the other remains on Earth. A naive analysis from both perspectives yields contradictory conclusions: each twin predicts the other would be younger. This apparent contradiction forms the core of the paradox. The paradox can be completely resolved within the framework of special relativity without needing to invoke general relativity. This research uses a library research method by collecting data from various relevant sources that support the twin paradox in the concept of time expansion. Experimental verification through the Hafele-Keating experiment with atomic clocks and observations of atmospheric muon decay confirms the theoretical predictions.